Preparação, caracterização e aplicação de asfalto modificado por madeira/borracha: execução em pista experimental em Macapá-AP - COELHO, Johnny Gilberto Moraes (Universidade Federal do Pará, 2019)
In order to mitigate environmental damage, companies have begun to use eco-friendly asphalt made from recycled material, which cannot be applied in the Amazon region or along the equator due to its instability. The primary objective of this study is to conduct a technology evaluation of combining hardwood waste used in civil construction with reused tire rubber for application in asphalt paving. A patent was generated (BR102016006187-3) to prepare the wood/rubber compound. A local petroleum asphalt cement binder was used (CAP 50/70), produced by PETROBRAS at the Fazenda Alegre field in Espírito Santo state and processed by LUBNOR in Fortaleza, Ceará state. The stone aggregates used were supplied by ETECOM LTDA. The grading curve used for the mixtures was range C, in line with the National Department for Transport Infrastructure (DNIT). The conventional asphalt and wood/rubber-modified mixtures were designed and analyzed in accordance with the Marshall method. The characteristics and behavior of the mixtures resulted in stability and tensile strength four and two-fold greater, respectively, than the normalized minimum value, with a small gain for the wood/rubber-modified mixtures and no significant change in apparent density or air void content. However, 40% more compaction energy was needed to achieve the same void volume without compromising asphalt durability. Replacing a portion of the mineral aggregates with the wood/rubber compound increased the flexibility of the asphalt mixture with a rise in tensile strength and decreased modulus of resilience in the hot-mix asphalt concrete (HMA) mixtures. For the asphalt mix designs, the desired low modulus of resilience to tensile strength ratio (RM/TS) was obtained by inserting wood/rubber at a value of 5159.26 (dimensionless), compared with the conventional value of 6607.67 (dimensionless). The experimental roads were paved at around 165 °C for the conventional asphalt mixtures and 170 °C for their modified counterparts, with no additional difficulties. The road paved with eco-friendly asphalt exhibited better stability (10.43 kN) than conventional asphalt (8.48 kN) after 50 months of use in Macapá, Amapá state (AP), Brazil.